A construção de representações sobre o trabalho docente: o papel do estágio - Bueno, Luzia (2007)
This research has as a far-reaching objective to contribute for a reflection about the period of probation on teachers initial formation during the graduation period by means of the analysis and the interpretation from constructed representations about the teacher s work on the texts worked out in detail to orient the probationer in his tasks and texts produced by his own initiative during the probation period. To accomplish this study, we have adopted the theoretical presupposition of the so-called Social-Discursive Interactionism (SDI) (Interacionismo Sóciodiscursivo ISD) that assigned to actions and to the language a fundamental role in the human development. In the SDI, the work is defined as a form of acting whose representations are constructed in the language. In this way, the work consists of one of the central spaces of the human being development in the current society. Thus, when we study texts that bring representations on the probation period work, we are also contributing for a better comprehension dealing with the human and professional development during the graduation. This comprehension can help either the formation courses specifically in a Language Course as well as all the ones that use the probation period and the production of texts as a manner to assure the probationer s professional development. With these objectives, we have presented in our work: a) a discussion about the probation period and the devices of formation used; b) a synthesis of the methodological theoretical presuppositions on which we consider the SDI theoretical chart and the procedures of the human actions analysis represented on the texts besides the contributions of recent researches used in the Work Science (Activity Ergonomics and Activity Clinic) in order to construct a wider vision about the educational work beyond the teacher s relation with the knowledge and his pupils. In the methodology, we have presented the data collected in a Language College from a private University in São Paulo State. They were consisted of a probation period orientation document and ten projects produced by the probationers in a discipline called Supervised Probation Period in Portuguese Language (Estágio Supervisionado em Língua Portuguesa). As analysis procedures, we have looked for verifying in each text its wider production context; internal questions organization, enunciative mechanisms and semantic characteristics in the organization and interpretation of acting in the work. All this have allowed detecting figures of action , indicating either the ways of saying the actions or ways of actions in the teacher professional category. Our analyses results have verified by means of the constructed figures of actions that either the orientation probation period document or the projects have presented a reduced vision concerned to the teacher s work and his role, retracting him as a general manner and distant from the reality in which the probationer should observe in a stage that proposes to form a teacher. We have also noticed that when planning the classes is this reduced vision that the probationer reacquires and forgets the practical activities that he has accomplished in the probation period with a real teacher and modeling his action only from readings. In this way, we have verified that the probationer s actions have the origin in the theoretical read texts and not in the practical activities that he has participated. Thus, these results obliged us to do a reflection about the form of orientation in the probation period and in the projects production that can lead the probationer to know different discourses in order to assume the interpretative debate among various positions to construct his own position as a professional